Upcycling used lottery tickets: extraction, characterization, and life cycle assessment of cellulose nanofibers using a cradle-to-gate approach - Madhu, Athulya K.; Rosa, Derval Santos; de Oliveira, Sueli Aparecida; Ajithkumar, T. G.; Parameswaranpillai, Jyotishkumar; Badawi, Michael; Dominic, C. D. Midhun (Materials Chemistry and Physics, 2026)
This work examines a sustainable approach for the isolation, characterization and Life Cycle Impact Assessment of cellulose nanofibers derived from post-consumer lottery tickets. The lottery tickets were subjected to bleaching using 15% H2O2 and 10% NaOH in a 5:1 ratio at 80 degrees C, followed by acid hydrolysis using 5% oxalic acid assisted with steam explosion. The isolated cellulose nanofibers were 16 to 36 nm diameter range with a crystallinity index of 84.5%. The zeta potential value of-25.19 mV revealed moderate colloidal stability for nanocellulose suspension. The thermal stability of nanocellulose fibers was reported around 300 degrees C in N2 atmosphere. The films fabricated from the nanocellulose fibers reported a tensile strength of 4.6 +/- 0.90 MPa. The cradle-to-gate Life Cycle Impact Assessment revealed the impact of electricity consumption and bleaching process on the isolation of nanocellulose from waste lottery paper. These findings underline the potential of waste-derived CNFs for sus-tainable applications such as biodegradable packaging while promoting circular economy principles and green nanotechnology through waste valorisation, eco-friendly chemistry, and life cycle sustainability.
Keywords: Cellulose nanofibers (CNFs); Life cycle impact assessment; Lottery tickets; Waste to wealth